PAREMIOLOGICAL UNITS WITH DIFFERENT ASPECTS - Mirzababyeva K. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article is devoted to the problem of a comprehensive description of paremiological units from the standpoint of philology. Paremiological units are widely used in society since ancient times. In ancient times, people did not have the opportunity to put their thoughts in written form. They had to remember catchy sayings similar to the paremiological units. Consequently, such sayings as the norm of society were spread orally from generation to generation, and subsequently renamed as "paremia" or "paremiological unit".